The mother of all pregnancy books - Douglas, Ann (2002)
Este texto contiene los siguientes temas: Are you ready to have a baby?, You pre-game plan, Sperm-meet egg, Missedconceptions, Winning al baby roulette, Operation healthy baby, The worry zone, The complaint department, To test or not to test?, Lights-camera-action!, When pregnancy isn'tperfect, Life after baby
Keywords: Embarazo